Functional investigation of zero lead radial shaft seal counter-surfaces turned with a special method. (February 2018) - Thielen, Stefan; Magyar, Balázs; Sauer, Bernd; Schneider, Frank; Mayer, Patrick; Kirsch, Benjamin; Müller, Ralf; Harbou, Erik v.; Aurich, Jan C.
Abstract: The sealing capabilities of RSS do not only depend on the seal itself but also on the lubricant and the shaft surface. A twist structure on the surface can cause pumping of the fluid during shaft rotation which can result in leakage. In this paper a special, new turning method, which consists of at least two turning steps with feed in reciprocal direction, is presented as an alternative to the conventional manufacturing process. The goal is to create a surface structure with a net pumping rate of zero. Shafts turned with the new proposed method are compared to turned shafts from previous investigations [1]. Criteria for the comparison are the surface pumping rate, leakage and wear behavior of the surface. Abstract : Highlights: Turning of radial shaft seal counter-surfaces. Superposition of two counteracting lead structures. Evaluation based on pumping rate and wear.